I wish I was an elephant - Bove, Jennifer, 1973- (New York, NY Harper, an imprint of HarperCollinsPublishers, 2018)
Explore the lives of elephants with Ranger Rick in this beginning reader with full-color photos of elephants in the wild! What if you wished you were an elephant and then you became one? Could you talk like an elephant? Sleep like an elephant? Live in an elephant family? And would you want to? Find out! Ranger Rick explorers can learn all about elephants in this reader full of fascinating facts, vivid wildlife photographs, a Wild Words glossary, and a hands-on activity about how to play "elephant hockey" using your arm like an elephant trunk. Ranger Rick: I Wish I Was an Elephant is a Level One I Can Read, which means it's perfect for children learning to sound out words and sentences.
"Ranger Rick books."
004-008.
Guided reading level M.
108844
Keywords: Elephants -- Juvenile literature; Juvenile Nonfiction -- Animals -- Elephants; Readers (Primary)